Analytical Performance of Quantitative DiaSorin Liaison SARS-COV-2 Antigen Test for the Asymptomatic Population - Gema Fernández-Rivas; Gema Fernández-Rivas; Jaume Barallat; Victoria Gonzalez; Victoria Gonzalez; Victoria Gonzalez; Silvia Martinez; Antoni E. Bordoy; Laura Jimenez; Cristina Casañ; Ignacio Blanco (Frontiers Media S.A., 2022)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) antigen (Ag) tests have been widely employed to identify patients for a rapid diagnosis and pandemic control. Rapid lateral-flow techniques are currently the most used, but automated technologies have emerged as another viable alternative to molecular methods. We aimed to evaluate the analytical performance of the DiaSorin Liaison SARS-CoV-2 Ag test in asymptomatic population and close contacts, for its use as a tool in pandemic control efforts.Material and Methods: A retrospective study was conducted. A total of 861 samples were included, 291 (34%) were positive for SARS-CoV-2 with cycle threshold (Ct) <40, and 570 (66%) were negative.Results: A strong correlation was observed between reverse transcriptase-PCR (RT-PCR) Ct and Ag 50% Tissue Culture Infectious Dose per milliliter (TCID50/ml; r = 0.6486; p < 0.0001) and all RT-PCR negative samples tested negative for the 200 TCID50/ml SARS-Cov-2 Ag cutoff, i.e., a specificity of 100% was reached (95% CI: 99.4-100.0%). Samples with <25 Ct and/or >106 extrapolated copies/ml were reached a sensitivity of 100% (95% IC 97.0-100.0%). For intermediate viral loads (>105 extrapolated copies/ml or <30 Ct), the sensitivity value still exceeded 80%. As with other Ag methods, samples between 30 and 40 Ct could not be detected with a reliable sensitivity.Conclusions: The LIAISON® SARS-CoV-2 Ag assay displays an acceptable sensitivity and a very high specificity that is useful for detecting the presence of SARS-CoV-2 in nasal swabs (NPS) of asymptomatic population or to regular monitoring of risk groups in controlled settings. Additionally, the flexibility in processing different samples and in the sampling preparation process makes this test an option for its use in high throughput laboratories. Automated tests may facilitate result reporting and yield consistent data, while avoiding some of the pitfalls of rapid lateral-flow techniques, such as observer variability.